Conventionality control in Argentine case law - Lucía Bellocchio (Revista de Direito Econômico e Socioambiental)
The article addresses the concept of conventionality control, its elements and characteristics, as defined by the Inter-American Court of Human Rights and Latin American supreme courts, and then analyze, in particular, the case of the jurisprudence of the Supreme Court of Justice of the Argentine Nation on the subject.